Is it Necessary to initiate antibiotic therapy in children with pharyngitis? - Danaei, Navid; Jafari, Mona; Ghorbani, Raheb; Jandaghi, Elahe (Archives of Advances in Biosciences, 2015)
Streptococcuscus Beta Hemolytic Group A is the most important pathogen causing which may lead to purulent and non purulent angina. Rheumatic fever is the most important complication that is the cause of 30% to 40% of cardiac disease and disablement. This study was performed to evaluate prevalence of Streptococcuscus Beta Hemolytic Group A and estimate role of clinical findings in children with Streptococcuscus angina diagnosis. antibiotic resistance was also assessed evaluated in the patients with bacterial pharyngitis. Throat culture was performed on 104 patients referred to Amiralmomenin hospital of Semnan at the age range of 5 to 15 years having angina without begin on antibiotic treatment after the completion of the questionnaire. A frequency of 1% have been assessed for Streptococcuscus Beta Hemolytic Group A, coagulase -positive Staphylococci and non-group A Streptococcuscus frequencies were 10.6% and 17.3% respectively. 100% of patients had pharyngeal erythema, 72% had fever, 55% had exudates and 52% had cervical adenopathy. The diagnosed Streptococcuscus was sensitive against penicillin, erythromycin and amoxicillin and resistant against cotrimoxazole. In examining Staphylococcus aureus antibiotic-resistance, only 40% of cases were sensitive to clindamycin and 40% were also sensitive to vancomycin. Very low frequency of group A Streptococcuscus has undermined the routine use of antibiotic and show that the clinical based diagnosis alone is not reliable and rational use of antibiotics requires the use of other diagnostic methods such as throat culture and rapid antigen test (RATs). Also in analyzing coagulase -positive Staphylococci antibiotic resistance, we can see increased cases of resistance against neomycin and clindamycin which indicates the necessity of rational treatment of patients afflicted by strep to coccal infections.